Early‐onset and very‐early‐onset bipolar disorder: distinct or similar clinical conditions?. (18th November 2015) - Propper, Lukas; Ortiz, Abigail; Slaney, Claire; Garnham, Julie; Ruzickova, Martina; Calkin, Cynthia V; O'Donovan, Claire; Hajek, Tomas; Alda, Martin
Abstract : Objective: This study aimed to examine differences in the clinical presentation of very‐early‐onset (VEO) and early‐onset (EO) bipolar disorder (BD) not fully explored previously. Methods: We selected two groups of subjects with BD from the Maritime Bipolar Registry based on age at onset of first major mood episode (VEO with onset prior to age 15 years; EO ranging from 15 to 18 years) and compared them with a reference group (onset after 18 years of age). There were 363 subjects (240 with bipolar I disorder and 123 with bipolar II disorder; mean age 44.2 ± 12.8 (SD) years), with 41 subjects in the VEO and 95 in the EO groups. Results: In comparison with the EO and reference groups, more subjects in the VEO group developed major depression as an index episode (88% for the VEO group versus 61% for the EO group and 54% for the reference group), and had an unremitting clinical course (65% versus 42% and 42%, respectively), rapid cycling (54% versus 34% and 28%, respectively), and comorbid attention‐deficit hyperactivity disorder (17% versus 1% and 3%, respectively); a higher proportion of the VEO group had first‐degree relatives with affective disorders compared with the EO and reference groups (0.41 versus 0.32 and 0.29, respectively), and they had lower scores on the Global Assessment of Functioning scale (mean scores of 64 versus 70 and 70). Overall, the EO group was similar to the reference group on most measures, except for increased suicidal behavior VEO 53%, EO 44% and reference group 25%). The results of polychotomous logistic regression also support the view that VEO BD represents a rather specific subtype of BD. Conclusions: Our results suggest the recognized correlates of early‐onset BD may be driven by subjects at the lowest end of the age at onset spectrum.